應用多媒體行動學習系統輔助大學生情緒管理學習成效與評量之探究 Exploration of Learning Effectiveness and Assessment of Emotion Management for College Students by Using a Multimedia Mobile Learning System - 張菀珍 Wan-Jen Chang; 葉榮木 Zong-Mu Yeh (National Taiwan Normal University, 2014)
本研究目的主要在分析運用多媒體行動學習系統結合課堂教學，以輔助大學生情緒管理的學習成效。多媒體行動學習系統是以Moodle 平台連結Android 智慧型手機，加上多媒體教材、即時簡訊、學習教材及Facebook互動論壇等功能模組所發展的情緒管理學習系統；同時，以多級模糊推論系統輔助大學生對情緒管理情境學習各階段的質性反思之學習評量。本研究採用準實驗設計法，對實驗組及對照組共72 位大學生進行教學實驗，並進行學習成效、系統滿意度及反思學習成效問卷的統計，研究結果發現：一、多媒體行動學習系統結合課堂教學能有效提升大學生情緒管理的學習成效；二、大學生對多媒體情緒管理行動學習系統的評價介於滿意和非常滿意之間；三、採用多級模糊推論系統輔助教師以彈性比例評量學生反思學習成績，可以減輕評量負擔。 This study analyzed the learning effectiveness of emotion management for college students through the application of a multimedia mobile learning system combined with classroom teaching. We used the Moodle platform, which is compatible with the Android operating system, and added several functional modules to the platform to enable students to learn effectively. The modules that constituted the emotion-management learning system comprised multimedia, instant messaging, learning materials, and a Facebook discussion forum. A multistage fuzzy system was used to assess students' qualitative reflections at various stages of the emotion-management learning process. A quasi-experimental design was used to investigate 72 college students. They were divided into an experimental group and a control group. The questionnaires on learning effectiveness and the students' satisfaction with the multimedia mobile learning system were statistically analyzed. According to the results: (1) the proposed multimedia mobile learning system combined with classroom teaching effectively improved the learning of emotion management; (2) the overall satisfaction of college students with the multimedia mobile learning system was between satisfied and very satisfied; and (3) we develop a multistage fuzzy system to reduce the burden of elasticity proportion assessment of the students learning emotion management through situational reflection.